What Else Do We Not Know About Teaching Polish Literature? A Literary Text During a Lesson of Polish Taught as a Foreign Language - Cyzman, Marzenna (INSTED: Interdisciplinary Studies in Education & Society, 2011)
Teaching Polish as a foreign language is booming. What qualifies to make such a statement is the growing number of better and better coursebooks created on the basis of communicative approach, the increased number of methodological studies, where efforts are made to describe the character of teaching our language and the growing number of organizations, not only of university type, which offer courses for foreigners and postgraduation studies of teaching Polish as a foreign language. During lessons of Polish language the most modern techniques of communicative approach are used, which guarantees more effective acquisition of our very difficult flexive language by foreigners. However, there is a certain area where not much research has been done so far: there is still a shortage of satisfactory comprehensive methodological proposals of teaching literature. Therefore, it is worthwhile considering where this worrying shortage results from and making an attempt to formulate at least a few methodological directives, which could be translated into a modern curriculum of teaching Polish as a foreign language.